Daruju (Acanthus ilicifolius L.) May Exhibit Anti-Breast Cancer Activity Through Inhibition of Proliferation Regulators: A Computational Study: Daruju (Acanthus ilicifolius L.) as Anti-Breast Cancer Agent - Rosyadah, Nuraini; Kamila, Fairuz Sarah; Hermanto, Feri Eko; Widyananda, Muhammad Hermawan; Grahadi, Rahmat; Dwijayanti, Dinia Rizqi; Widodo, Nashi; Ulfa, Siti Mariyah (Journal of Tropical Life Science, 2025)
Breast cancer's increasing prevalence globally underscores the urgent need for effective and gentle therapies, positioning the exploration of herbal remedies as a critical pursuit. Daruju (Acanthus ilicifolius L.) emerges as a compelling candidate due to its inherent bioactive components. This research pioneers the application of advanced computational techniques to unveil the latent anti-breast cancer potential within A. ilicifolius. Our in-silico investigation commenced by cataloging A. ilicifolius compounds using the KNApSAcK database and existing literature. These compounds underwent rigorous screening for drug-like characteristics via SWISS-ADME and potential biological activity using PASS ONLINE. Protein targets relevant to breast cancer were predicted through SWISS Target and the STRING database, integrated with Cytoscape for network visualization. Molecular docking, performed with PyRx 0.8, assessed the binding strength between the identified compounds and target proteins, with the most promising interactions selected for further scrutiny. The stability of these crucial interactions was then evaluated through molecular dynamics simulations using YASARA. This comprehensive computational strategy aims to pinpoint potential anti-breast cancer agents derived from A. ilicifolius. Initial analysis of 17 compounds from A. ilicifolius, based on chromatography, databases, and prior studies, narrowed down to five that adhered to Lipinski’s Rule of Five for drug-likeness: 4-O-beta-D-glucosyl-4-coumaric acid, (-)-lyoniresinol, α-amyrin, adenosine, and p-coumaric acid. These compounds were predicted to directly interact with key breast cancer-related proteins across pathways like estrogen signaling, JAK/STAT, and PI3K/AKT. Notably, molecular docking revealed strong binding affinities for α-amyrin with CDK4, ER, and EGFR (-7.5 kcal/mol, -9.5 kcal/mol, and -8.7 kcal/mol, respectively), comparable to known inhibitors. Molecular dynamics simulations further corroborated the stability of these complexes, analyzing RMSD and binding affinity parameters. Consequently, α-amyrin stands out as a promising anti-breast cancer agent within A. ilicifolius, exhibiting potential to inhibit proteins crucial for breast cancer cell proliferation and survival, including CDK4, ER, and EGFR.